Effects of different salt sources and salinity levels on emergence and seedling growth of faba bean genotypes - Nurlykhan Bimurzayev (Nature Portfolio, 2021)
Abstract Suitability of poor quality water for irrigation depends on salinity level and solute concentration in the water and selected crop. Salt stress is a major potential constraint for faba bean. The present study aimed to investigate the effects of different Cl- and SO4-containing salt sources in irrigation water with different salinity levels on emergence, early seedling growth and photosynthetic capacity of six faba bean genotypes. The negative effect order of salinity level was high (3 dS/m) > medium (2 dS/m) > low (1 dS/m) > control (0.05 dS/m) for all investigated parameters except dry root weight. The negative effects of Cl-containing salt sources were higher than that of SO4-containing salt sources. The worst and the best performing genotypes were determined as III-28 and III-29 on emergence percentage at 10th DAS, I-29 and III-1 on mean emergence time, III-22 and III-1 on shoot height, III-1 and I-29 on fresh biomass weight, III-22 and III-28 on fresh shoot weight, III-29 and I-29 on fresh root weight, respectively. This study showed that faba bean genotypes have different behaviors in terms of response to the increasing salinity levels artificially makeup by using different salt sources indicating that salt response of faba bean is genotype-specific.